An enquiry of English learning materials appropriacy for nautical students - Sari, Ardiana; Hamka, Ade; Sari, Afia; Ratnaningsih, Dyah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
Nautical students are required to have communicative competence in English that will be beneficial for their future careers. However, the teaching and learning implemented remain insufficient in terms of sources, learning topics, and learning materials. Therefore, the present study aims to investigate teacher’s and students’ preferences in teaching English for Specific Purposes (ESP) and elaborate the learning needs. This study utilizes a mix-methods approach which involves fifty-three nautical students and an ESP teacher at a maritime polytechnic located in East Java. The needs analysis was conducted by distributing online questionnaires containing three sections, such as (1) students’ current level of English competency, (2) skills priorities, and (3) learning topics needs. The semi-structured interview was conducted virtually with the teacher. The results of the questionnaire and interview were synthesized and summarized. The findings demonstrate that students’ English proficiency is at beginner to low intermediate level. Furthermore, speaking is stated as the most imperative skill among the students. However, in order to maximize speaking ability, the development of listening topics and sources is required. In addition, some developments for other skills are also required due to the inadequacy and unavailability of learning topics in the syllabus. Future research is worth conducting aiming at developing the ESP syllabus for Nautical students. Kesesuaian materi pembelajaran bahasa Inggris untuk mahasiswa pelayaran Siswa pelayaran dituntut untuk memiliki kompetensi komunikatif dalam bahasa Inggris yang akan bermanfaat untuk karir mereka di masa depan. Namun, pembelajaran yang dilaksanakan masih belum memadai dari segi sumber dan bahan ajar. Oleh karena itu, penelitian ini bertujuan untuk menyelidiki preferensi guru dan siswa dalam mengajar English for Specific Purposes (ESP) dan mengelaborasi kebutuhan pembelajaran. Penelitian ini menggunakan pendekatan metode campuran yang melibatkan lima puluh tiga mahasiswa pelayaran dan seorang guru ESP di sebuah politeknik pelayaran yang terletak di Jawa Timur. Analisis kebutuhan dilakukan dengan membagikan kuesioner online yang berisi tiga bagian, yaitu (1) tingkat kompetensi bahasa Inggris siswa saat ini, (2) prioritas keterampilan, dan (3) kebutuhan materi pembelajaran. Wawancara semi-terstruktur dilakukan secara daring dengan guru. Hasil kuesioner dan wawancara disintesis dan dirangkum. Temuan menunjukkan bahwa kecakapan bahasa Inggris siswa berada pada tingkat pemula hingga menengah rendah. Selanjutnya, berbicara dinyatakan sebagai keterampilan yang paling penting di kalangan siswa. Namun, untuk memaksimalkan kemampuan berbicara, diperlukan pengembangan bahan dan sumber menyimak. Selain itu, beberapa pengembangan keterampilan lain juga diperlukan karena ketidakcukupan dan tidak tersedianya topik dan materi dalam silabus. Penelitian di masa depan perlu dilakukan dengan tujuan mengembangkan silabus ESP untuk siswa pelayaran.